Сони рода Ramys (Rodentia, Gliridae) позднего валлезия Украины - Несин, В.А. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Описаны сони двух видов рода Ramys Garcia-Moreno & Lopez-Martinez, 1986: R. multicrestatus de Brujin и R. gipa-nensis Nesin, sp. n. позднего валлезия Украины из местонахождения Михайловка 1. The remains of two glirid species of the genus Ramys Garcia-Moreno & Lopez-Martinez, 1986 from the late Vallesian locality Mikhailovka 1 (Ukraine) are described. R. multicrestatus de Brujin was not known previously in the region. R. gipanensis Nesin, sp. n. is described.